A design of new miniaturized MMIC low pass filter / Nurul Husna Md Yusoh - Md Yusoh, Nurul Husna (2014)
In this paper, a new miniaturized MMlCs low pass filter with reduce size design is being discussed. The multilayers configured with gallium arsenide (GaAs) as a substrate while the polyimide layer as dielectric. The filter consists of buried coplanar layer and a polyimide overlay and has overall area of 160 x 120 //in2. An electromagnetic simulator Sonnet Lite is used to characterize and predict the filter response. The results of this simulation show that the filter well operates without spurious in the passband or stopband. The results also revealed that these miniaturized structure are appropriate for low cost and low loss which are smaller than that of conventional equivalents. By using the same structure three different cut-off frequencies has been obtained with three different sizes of transmission line. The simulation results show all the values of insertion and return losses.